1997
DOI: 10.1254/jjp.73.73
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Anti-Glomerular Basement Membrane Nephritis in Rats by ONO-1301, a Non-Prostanoid Prostaglandin I2 Mimetic Compound with Inhibitory Activity against Thromboxane A2 Synthase.

Abstract: ABSTRACT-The antinephritic effects of ONO-1301 ([7,8-dihydro-5-[(E)-[[a-(3-pyridyl)benzylidene] aminooxy]ethyl] -1-naphtyloxy]acetic acid) on crescentic-type anti-glomerular basement membrane (GBM) nephritis in rats were investigated. ONO-1301 was orally given to crescentic-type anti-GBM nephritic rats for 40 days after the induction of nephritis. ONO-1301 (30 mg/kg) suppressed the elevation of protein ex cretion into urine. In the ONO-1301-treated rats, cholesterol and urea nitrogen content in the plasma was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…2). Moreover, we found that ONO-1301 (IP receptor agonist) (Hayashi et al, 1997;Imawaka and Sugiyama, 1998) strongly prevented the expression of ICAM-1, B7.2, and CD40 in the presence and absence of IL-18 ( Fig. 2) but had no effect on the expression of B7.1 and CD40L (data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…2). Moreover, we found that ONO-1301 (IP receptor agonist) (Hayashi et al, 1997;Imawaka and Sugiyama, 1998) strongly prevented the expression of ICAM-1, B7.2, and CD40 in the presence and absence of IL-18 ( Fig. 2) but had no effect on the expression of B7.1 and CD40L (data not shown).…”
Section: Resultsmentioning
confidence: 82%
“…The regimen used in the experiments was determined from those used in previous papers. [8][9][10][11][12] Animals and cardiac transplantation: Male inbred mice (4 to 6 weeks, 20-25 g) were used. The male BALB/c (H-2 d ) and C57BL/6 (H-2 b ) mice (4-6 weeks, 20-25 g) were obtained from Japan Clea, Co (Tokyo), and this combination was used as the major histocompatibility complex total allomismatch group for analysis of acute rejection.…”
Section: Methodsmentioning
confidence: 99%
“…6) Because ONO-1301MS does not have prostanoid structures, it is not easily metabolized and its effects remain for a longer time compared with other prostacyclin analogs, such as beraprost or iloprost. [7][8][9][10] It has been reported that local administration of a slow releasing form of ONO-1301MS into ischemic murine hearts was effective at preventing left ventricular remodeling and improving the survival rate.…”
mentioning
confidence: 99%
“…First-strand cDNAs were synthesized using SuperScript III Reverse Transcriptase (Invitrogen, Carlsbad, USA) with oligo(dT) [12][13][14][15][16][17][18] primers. The primer sequences for mRNA quantification are listed in Fig.…”
Section: Rna Preparation and Quantitative Rt-pcrmentioning
confidence: 99%
“…Previous studies using animal models of tissue fibrosis have provided evidence that HGF exerts anti-fibrotic actions on tissue fibrosis, including liver fibrosis/cirrhosis (20,27,35). ONO-1301 was developed as a new type of prostaglandin I 2 (PGI 2 )/IP receptor agonist lacking the typical prostanoid structures, including a 5-membered ring and allylic alcohol (12). Prostacyclin and its analogues are not stable in vivo, whereas ONO-1301 is chemically and biologically more stable than prostacyclin and its analogues because of the absence of prostanoid structures.…”
Section: Rna Preparation and Quantitative Rt-pcrmentioning
confidence: 99%